The Effect of Media Flip PDF Corporate Edition to Increase Interest in Learning Social Sciences in Elementary School - Aisah, Sintiya Rizki; Shidiq, Galih Albarra; Widiyan, Agung Purwa (IJCAR: Indonesian Journal of Classroom Action Research, 2023)
In the 21st-century education is marked by technological developments marked by increasingly close relations between science and technology, accelerating the synergy between the two. Technological developments in the world of education are expected to be a means of developing more optimal education. Technological development in the 4.0 era is relevant to meeting educational needs in the 21st century. One of the technological developments in learning in education is using Flipbook learning media based on Flip PDF Corporation Edition. Through media Flip PDF Corporate Edition, students received experience more exciting learning with the features presented, being able to interact with students to make learning more meaningful. After the Covid-19 pandemic, changes in student interest in education impacted learning; for this reason, educators need to innovate by utilizing Flip PDF Corporate Edition media to increase student interest in learning so that later it will also affect student learning outcomes.